Kedudukan Hukum Masyarakat Adat Dalam Memperoleh Hak Atas Tanah di Indonesia - Arvita Hastarini (Jurnal Hukum Sasana, 2022)
Since the first, land rights have been important for people in any part of the world, including indigenous peoples of Indonesia. However, indigenous peoples in Indonesia continue to be in a weak position in the pursuit of land rights and access to natural resources. In fact, the position of indigenous peoples in obtaining land rights is recognized and protected by the constitution contained in the 1945 Constitution and Law Number 5 of 1960 concerning Basic Agrarian Regulations (UUPA). Therefore, this study wants to know how the legal position of Indigenous Peoples in obtaining Land Rights based on the positive law of the draft land laws and regulations in Indonesia and how the process of submitting an application for indigenous peoples in obtaining joint property rights over the land of an indigenous peoples who are in certain areas in Indonesia. The research was structured using a normative juridical research method using a statutory approach that will examine and analyze the application of the rules or norms in various laws and regulations and also in the Land Bill which will become a new legal product and various literatures. others as a resource that can help in answering all existing problems.